The power of commitment: How can high commitment work system build eesilience, combat stress and cynicism - Sehrish Abro; Zahid Ali Chanar; Pireh Sikandar; Sundus Rahim (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
This study investigates the effects of high commitment work system (HCWS) on reducing employees' psychological negativities like work stress and organizational cynicism through developing psychological capacities like employees' resilience, a moderated mediation model is adopted to understand moderating role of occupational self-efficacy on the mediated relationship. Based upon positivist research philosophy and deductive approach, a close -ended survey questionnaire was adapted from different sources and used for data collection. The PLS-SEM technique was used to analyze the data in SmartPLS4. The results reveal that HCWS is significantly and negatively related to work stress and organizational cynicism. Furthermore, HCWS builds upon employee resilience which in turn negatively predicts occupational stress and cynical attitude among employees. The findings also suggest that interaction between HCWS and high occupational self-efficacy will further enhance the impact on work stress and cynicism via resilience. The study highlights the importance of promoting a positive work culture to support the wellbeing of organizational members and mitigate negative psychological effects.
Keywords: 330; High commitment work system; employee resilience; work stress; organizational cynicism; occupational self-efficacy; health care professionals